The Growth Enhancement Potentials of Indigenous Plant Growth Promoting Rhizobacteria on Sweet Pepper (Caspicum annum) through Seed Bacterization - Ajibade Oluwatosin Akinola; Taiwo Toba Timothy; Olotu Titilayo Mabel; Alao Jude Oluwapelumi; Oyetunde Oluwapelumi Breakthrough; Oladapo Ifeoluwa David; Omotayo Joseph Olusegun; Stanford Kwenda; Zamantungwa Khumalo; Arshad Ismail; Oloke Julius Kola; Oyawoye Olubukola Monisola (International Journal of Scientific Research and Innovative Studies, 2022)
The demand for food is rising as the world's population is rising. The second sustainable development goal's objectives of achieving global food security and agricultural sustainability call for swift and coordinated action. The use of traditional mineral fertilizers has increased dramatically in response to the rise in food demand, but this has its drawbacks. Plant growth-promoting rhizobacteria (PGPR) which is a free-living bacteria actively colonize plant roots and aids it growth. They provide an environmentally friendly way to boost plant output. Due to the high nutritional content and wide range of medicinal applications of sweet pepper (Capsicum annuum L.), it constitute one of the most significant vegetable crops in the world.. sweet pepper (Capsicum annum ) was evaluated through a pot study under the treatment of six bacterial strains. Bacterization of sweet pepper seeds was done via the immersion of seeds in a suspension of bacteria (108 CFU/ml) modified with 2% carboxymethyl cellulose (CMC), The treated seeds were planted in sterilized planting bags with sterilized sand, Effects of bacterized seeds of Capsicum annuum on the shoot height revealed that the highest shoot height was observed at week 8 by isolate AU4(Burkholderia sp) at (9.66±12.15), followed by AU6 (Burkholderia sp ) at week 6 (6.26±0.05). The highest leaf number of Capsicum annuum after bacterization was observed at week 8(9.00±0.0) and 10(9.00±0.0), while the observed control at week 8(6.00±1.0) week 10(7.00±0.0). Plant growth-promoting bacteria applied via seed bacterization has shown potential for increasing the growth parameters of sweet pepper. This could be a formidable substitute for the use of chemical fertilizers. The use of Burkholderia vietnamiensis AU2011 and Burkholderia sp have shown potential for the increment of the agronomical parameter of C. annuum.